Effects of Sodium‐Glucose Cotransporter 2 Inhibitors on 24‐Hour Ambulatory Blood Pressure: A Systematic Review and Meta‐Analysis. Issue 5 (May 2017) - Baker, William L.; Buckley, Leo F.; Kelly, Michael S.; Bucheit, John D.; Parod, Eric D.; Brown, Roy; Carbone, Salvatore; Abbate, Antonio; Dixon, Dave L.
Abstract : Background: Sodium‐glucose cotransporter 2 (SGLT2) inhibitors are a novel class of antihyperglycemic agents that improve glycemic control by increasing glycosuria. Additional benefits beyond glucose lowering include significant improvements in seated clinic blood pressure (BP), partly attributed to their diuretic‐like actions. Less known are the effects of this class on 24‐hour ambulatory BP, which is a better predictor of cardiovascular risk than seated clinic BP. Methods and Results: We performed a meta‐analysis of randomized, double‐blind, placebo‐controlled trials to investigate the effects of SGLT2 inhibitors on 24‐hour ambulatory BP. We searched all studies published before August 17, 2016, which reported 24‐hour ambulatory BP data. Mean differences in 24‐hour BP, daytime BP, and nighttime BP were calculated by a random‐effects model. SGLT2 inhibitors significantly reduce 24‐hour ambulatory systolic and diastolic BP by −3.76 mm Hg (95% CI, −4.23 to −2.34; I 2 =0.99) and −1.83 mm Hg (95% CI, −2.35 to −1.31; I 2 =0.76), respectively. Significant reductions in daytime and nighttime systolic and diastolic BP were also found. No association between baseline BP or change in body weight were observed. Conclusions: This meta‐analysis shows that the reduction in 24‐hour ambulatory BP observed with SGLT2 inhibitors is a class effect. The diurnal effect of SGLT2 inhibitors on 24‐hour ambulatory BP may contribute to their favorable effects on cardiovascular outcomes.